Illustrated human and social biology - Beckett, B. S. (New York : Oxford University Press, 1989)
Aiming to cover the main topics required by GCSE syllabuses in Human Biology, this textbook is also useful as a supplement for GCSE Biology courses. It provides a basic reference for students needing a grounding in Human Biology. It features clear explanations of important technical terms, a glossary, and vocabulary and comprehension tests.
Includes index.
Keywords: Human biology; Biology; Physiology